Exercise training combined with bifidobacterium longum OLP-01 supplementation improves exercise physiological adaption and performance - Huang, W.-C.; Hsu, Y.-J.; Huang, C.-C.; Liu, H.-C.; Lee, M.-C. (Nutrients, 2020)
Probiotics exert multiple health benefits, including gastrointestinal health, immunoregulation, and metabolic disease improvement, by modulating microbiota to maintain eubiosis via the hypothalamic-pituitary-adrenal (HPA) and brain-gut-microbiome axes. Physiological fatigue, mental stress, and gastrointestinal discomfort under the demands of athletic performance as well as immunosuppression are common during endurance training and competition. Limited studies investigated the functional effects of probiotic supplementation on endurance training. Bifidobacterium longum subsp. Longum OLP-01 (OLP-01), isolated from an elite Olympic athlete, was combined with a six-week exercise training program with gradually increasing intensity. In this study, Institute of Cancer Research (ICR) mice were assigned to sedentary, exercise, OLP-01, or exercise + OLP-01 groups and administered probiotic and/or treadmill exercise training for six weeks to assess exercise performance, physiological adaption, and related metabolites. The exercise + OLP-01 group demonstrated higher performance in terms of endurance and grip strength, as well as improved fatigue-associated indexes (lactate, ammonia, creatine kinase (CK), lactate dehydrogenase (LDH), and glycogen content), compared with the other groups. OLP-01 supplementation significantly ameliorated inflammation and injury indexes (platelet/lymphocyte ratio (PLR), aminotransferase (AST), and CK) caused by prolonged endurance exercise test. Moreover, acetate, propionate, and butyrate levels were significantly higher in the exercise + OLP-01 group than in the sedentary and OLP-01 groups. Athletes often experience psychological and physiological stress caused by programed intensive exercise, competition, and off-site training, often leading to poor exercise performance and gastrointestinal issues. Functional OLP-01 probiotics are considered to be a nutritional strategy for improving physiological adaption, oxidative stress, inflammation, and energy balance to ensure high physical performance. Based on these results, probiotics combined with exercise training is a potential strategy for ensuring high physical performance of athletes, which should be further investigated through microbiota validation.